2003
DOI: 10.1046/j.1365-2109.2003.00805.x
|View full text |Cite
|
Sign up to set email alerts
|

Weaning of juvenile pikeperch, Stizostedion lucioperca L., and perch, Perca fluviatilis L., to formulated feed

Abstract: Weaning success of pond‐cultured pikeperch and wild‐caught perch (mean length 51 and 48 mm respectively) was evaluated using different weaning techniques and different formulated feeds. Juveniles that were fed formulated feed grew as well as or better than juveniles that were weaned successively using zooplankton or yolk. Four different formulated feeds (agglomerated marine larvae feed, marine larvae feed, trout feed and a semi‐moist feed) were evaluated regarding specific growth rate (SGR), condition factor a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 16 publications
1
25
0
Order By: Relevance
“…Although growth performances were significantly low (P < 0.05) in larvae exclusively fed dry feeds, angel fish accepted formulated feed even at the first feeding without any additional weaning protocol. A similar trend has also been reported by Ljunggren et al (2003) for pike perch juveniles. Further, Carvalho et al 2006) also observed significant growth and survival (56%) in zebra fish larvae exclusively fed dry feeds.…”
Section: Discussionsupporting
confidence: 90%
“…Although growth performances were significantly low (P < 0.05) in larvae exclusively fed dry feeds, angel fish accepted formulated feed even at the first feeding without any additional weaning protocol. A similar trend has also been reported by Ljunggren et al (2003) for pike perch juveniles. Further, Carvalho et al 2006) also observed significant growth and survival (56%) in zebra fish larvae exclusively fed dry feeds.…”
Section: Discussionsupporting
confidence: 90%
“…Several studies deal with the rearing and feeding of pikeperch at the juvenile stage (Zakes 1997(Zakes , 1999Zakes et al 2001;Ljunggren et al 2003), but the experience in the rearing of the North American species (Stizostedion vitreum; Moore 1996;Summerfelt 1996;Guthrie et al 2000) is much more developed.…”
Section: Introductionmentioning
confidence: 98%
“…Former studies have shown that pike perch fingerlings of 0.5-1.0 g can be trained to accept formulated feed by gradual substitution of natural food sources (e.g. chironomids) with artificial diets over a period of 2-4 weeks (Zakes 1997;Kamstra et al 2001;Zienert and Wedekind 2001;Baer et al 2001;Ljunggren et al 2003;Schulz et al 2005). There are no specific feed formulations for pike perch yet, that pike perch are commonly fed, high energy diets primarily developed for salmonids.…”
Section: Introductionmentioning
confidence: 98%